2013
DOI: 10.14233/ajchem.2013.14870
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Environment Influence the Incidence of Childhood Autism

Abstract: This review summarizes the environmental factors in particular chemicals involved in autism with either increasing or reducing effect in disease incidence, which will be helpful for prevention and treatment of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…In general, this study indicated that ADHD caused the reduction in number of gut bacteria but increased the diversity of community, suggesting that the diversity of microbiome community may be related to the development of ADHD. Interestingly, the change of gut bacteria in ADHD is similar to that in ASD (autism spectrum disorder, another children disease) children in our previous studies (Yu et al, 2013(Yu et al, , 2020. This can be justified by the result of many studies, which have found that comorbidity is high in ASD and ADHD individuals (Bölte et al, 2014).…”
Section: Species Composition Determined By 16s Rrna Amplicon Sequencingsupporting
confidence: 69%
“…In general, this study indicated that ADHD caused the reduction in number of gut bacteria but increased the diversity of community, suggesting that the diversity of microbiome community may be related to the development of ADHD. Interestingly, the change of gut bacteria in ADHD is similar to that in ASD (autism spectrum disorder, another children disease) children in our previous studies (Yu et al, 2013(Yu et al, , 2020. This can be justified by the result of many studies, which have found that comorbidity is high in ASD and ADHD individuals (Bölte et al, 2014).…”
Section: Species Composition Determined By 16s Rrna Amplicon Sequencingsupporting
confidence: 69%
“…The latest research in childhood neurodevelopmental disorders, including ASD, has transferred from genetics to environmental factors in the gut microbiome, which plays an important role [ 1 , 28 , 29 ]. Indeed, many studies have described the changes of intestinal microbiota of ASD children using non-culture-based methods [ 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Autism spectrum disorder (ASD) is a severe neurodevelopmental disorder characterized by abnormal social interactions, impaired language, and stereotypical and repetitive behaviors [ 1 , 2 , 3 , 4 ]. In the last decade, more and more children have been diagnosed with ASD, which affects approximately 8–12% of children school-aged children worldwide [ 1 , 5 ]. Furthermore, the number of ASD children has also significantly increased in China in the last few years [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Autism spectrum disorder (ASD) is a severe neurodevelopmental disorder which is characterized by abnormal social interactions, impaired language, and stereotypic and repetitive behaviors. In recent years, ASD has become a public health problem with a prevalence rate of 0.6–1.7% in children, while the number of children diagnosed with ASD is quickly increasing around the world [ 1 , 2 , 3 , 4 , 5 ]. In order to elucidate the cause of this disease, many studies have described and compared the composition of gut microbiota in children with and without ASD [ 6 , 7 , 8 , 9 , 10 ], which provided strong support for the change in the gut microbiome of ASD children compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%